Danos do complexo broca-podridão à produtividade e à qualidade da cana-de-açúcar fertirrigada com doses de nitrogênio - Pannuti, Luiz Eduardo da Rocha [UNESP]; Baldin, Edson Luiz Lopes [UNESP]; Gava, Glauber José de Castro [UNESP]; Kölln, Oriel Tiago; Cruz, Juliana Cristina Sodário (FapUNIFESP (SciELO), 2013)
The objective of this work was to evaluate the effect of nitrogen-fertigation on the damage caused by the borer-rot complex to the productivity and quality of fertigated sugarcane. The experiment was carried out in field, using a randomized complete block design, with four replicates and five N doses (0, 50 100, 150, and 200 kg ha-1) applied through drip irrigation. The following variables were determined: number of holes caused by Diatraea saccharalis (Lepidoptera: Crambidae); number of internodes infected with red rot; incidence percentage of red rot; stalk productivity; and sugar content. In laboratory, the attractiveness and the consumption of culm fragments by fourth instar caterpillars, in trials with or without choice, were evaluated. Nitrogen fertigation increased the incidence of D. saccharalis and red rot. The number of holes produced by the larvae was correlated with the occurrence of red rot. Sugar percentage reduced with the increase in the number of red rot affected internodes. Nitrogen doses did not affect the attractiveness of sugarcane culm fragments; however, higher N doses increased the consumption of these fragments by D. saccharalis caterpillars. Despite the damages to quality, nitrogen fertilization expressively enhanced the productivity of stalks and sugar.

O objetivo deste trabalho foi avaliar o efeito da fertirrigação nitrogenada sobre os danos causados pelo complexo broca-podridão à produtividade e à qualidade da cana-de-açúcar. O experimento foi realizado em campo, em delineamento de blocos ao acaso, com quatro repetições e cinco doses de N (0, 50, 100, 150 e 200 kg ha-1), aplicadas por irrigação por gotejamento. Quantificaram-se as seguintes variáveis: número de orifícios causados por Diatraea saccharalis (Lepidoptera: Crambidae); número de internódios infectados com a podridão-vermelha; percentagem de incidência de podridão-vermelha; produtividade de colmos; e teor de açúcar. Em laboratório, foram avaliados a atratividade e o consumo de fragmentos de colmos por lagartas de quarto instar, em testes com ou sem chance de escolha. A irrigação nitrogenada aumentou a incidência de D. saccharalis e de podridão-vermelha. O número de orifícios causados pelas lagartas correlacionou-se à ocorrência de podridão-vermelha. A percentagem de açúcar diminuiu com o aumento do número de internódios danificados pela podridão-vermelha. As doses de N não afetaram a atratividade dos fragmentos de colmos de cana-de-açúcar; no entanto, maiores doses de N fertilizante aumentaram o consumo destes fragmentos por lagartas de D. saccharalis. Apesar dos danos à qualidade, a adubação nitrogenada aumentou expressivamente a produtividade de colmos e de açúcar.
Damages caused by the borer-rot complex to the productivity and quality of sugarcane fertigated with nitrogen doses